Fecal or bacterial transplantation in mice transfer environment-induced brain plasticity and associated behavioral changes - Marrocco, Francesco; Khan, Rizwan; Reccagni, Alice; Lin, Xingzi; Delli Carpini, Mary; Iebba, Valerio; D’Alessandro, Giuseppina; Limatola, Cristina (Frontiers in Physiology, 2025)
IntroductionRecent studies have shown that lifestyle factors, including diet and environmental stimuli, significantly alter the composition of gut microbiota and the metabolites they produce. Specifically, housing mice in an enriched environment (EE) enhances the production of short-chain fatty acids, which in part mediate the effects of EE on brain plasticity. In this study, we tested the hypothesis that the gut microbial composition of EE-exposed mice could be transplanted into mice housed in a standard environment (SE) to replicate the environmental effects on behavior, gene expression and neurogenesis.MethodsTo test this hypothesis, we transplanted either a specific bacterial mixture or fecal material from EE-housed mice into SE-housed mice.ResultsOur data show that both bacterial and fecal transplants reduce anxiety-like behaviors in mice. Additionally, we observed increased expression of hippocampal neurotrophins and enhanced neurogenesis.DiscussionThese findings support the idea that gut microbiota influence brain functions, including anxiety-like behavior. Further research is necessary to clarify the underlying mechanisms. Moreover, the results suggest that fecal material transplantation (FMT) from individuals with healthy lifestyles may represent a promising strategy for the treatment of mood disorders.